1981
DOI: 10.1007/bf00987710
|View full text |Cite
|
Sign up to set email alerts
|

Insect sex pheromones: Evaporation rates of alcohols and acetates from natural rubber septa

Abstract: The half-lives (t 1/2) of alcohol sex pheromones, 1-alkanols, acetate sex pheromones, and an epoxide (disparlure) were determined on natural rubber septa. Thet 1/2 values for the homologous alcohols from decanol to heptadecanol increased regularly from 2.2 to 1117 days, but thet 1/2 of octadecanol was 609 days. Thet 1/2 values of (Z)7-, (E)7-, and (Z)9-tetradecen-1-ol acetates were 154, 168, and 199 days, respectively, whereas those of five other tested 14-carbon acetates ranged from 310 to 350 days. The depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 6 publications
3
42
0
1
Order By: Relevance
“…The (initial) rate of emission of pheromone from the glass tube is higher than from most slow-release formulations. For example, the half-life of Z-7 : 12Ac on robber septa is 34.8-35.9 days (Butler and McDonough, 1979). Based on this half-life, the initial emission rate from a septum dosed with 1 mg is 6.1 • 10 .5/xmol/min.…”
Section: Resultsmentioning
confidence: 95%
“…The (initial) rate of emission of pheromone from the glass tube is higher than from most slow-release formulations. For example, the half-life of Z-7 : 12Ac on robber septa is 34.8-35.9 days (Butler and McDonough, 1979). Based on this half-life, the initial emission rate from a septum dosed with 1 mg is 6.1 • 10 .5/xmol/min.…”
Section: Resultsmentioning
confidence: 95%
“…Controlled-release pheromone lures have included cotton dental wicks, rubber septa, polyethylene vials, laminates, hollow fibers, membranes, and polymeric systems (13). Rubber septa have been the most widely used substrate for the controlled release of many insect sex pheromones (5,40). Flint et al (10) showed that rubber septa were an excellent substrate for the controlled release of gossyplure for pink bollworm Pectinophora gossypiella (Saunders), and rubber septa baited with codlemone have been the most common substrate for the codling moth (27).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore likely that changes in the pheromone blend in time and space explain the difference between wind tunnel and field experiments. In our experiment, it is proposed that the blend becomes slowly enriched in the alcohol, given that it is less volatile than the acetate 33,34 (Vp = 4.37E-4 torr and Vp = 6.35E-4 torr, respectively), 35 and it may therefore be concluded that soon after the experiment begun, the 15:1 (OH:Ac) initial mixture approximated to the 1:0, decreasing hence its attractivity, and that the 1:1 was enriched in the alcohol, becoming more similar to the blend that was most active in the wind tunnel. In fact, the 15:1 and 1:0 initial mixtures performed similarly throughout the experiment, and so did the 1:1 initial mixture towards the end (Figure 2), possibly due to a complete evaporation of the acetate.…”
Section: Resultsmentioning
confidence: 88%